Reification in the poor early childhood (Revista INTEREDU11, 2019)
Person’s reification implies a philosophical position that emerges from a direct opposite logic of meeting, in a neoliberal boundary and affection. Early Childhood public policies haven’t scape from it, and we can understand that this has built in a combination of neoliberal boundaries that emerges from public policies governability all through micro relationships in the early childhood schools.